An Insight into the Research Concerning Panax ginseng C. A. Meyer Polysaccharides: A Review. Issue 6 (18th August 2022) - Ji, Xiaolong; Hou, Chunyan; Shi, Miaomiao; Yan, Yizhe; Liu, Yanqi
ABSTRACT: Ginseng ( Panax ginseng C. A. Meyer) is known as a valuable traditional Chinese herb for tens of centuries. Previous pharmacological and phytochemical investigations indicate that polysaccharides are a main biologically active ginseng component that possesses different bioactivities such as antitumor, immunoregulation, antioxidation, hepatoprotection, and anti-inflammation. Work is needed to summarize the full aspects of these polysaccharides systematically to boost their further investigation and application. In this review, studies on the extraction, purification, characterization, and bioactivity are introduced in detail. Moreover, the structure–bioactivity relationship of ginseng polysaccharides is explored and discussed. The uronic acids richer in ginseng polysaccharides tend to have higher biological effect, and the α-(1→4)-Gal p A and α-(1→4)-Gal p in the main chain are essential for the anti-inflammatory and antiviral effects. We believe our work proposes a helpful bibliography for further innovation and promotes these natural products in functional food.